Implementación de un sistema fotovoltaico Off-The-Grid de 1,5 KW de potencia para alimentar dispositivos electrónicos en la Sala de Cómputo del bloque C de la Universidad Antonio Nariño sede Valledupar (2022)
Electric power is an important factor in today's world, since human beings have been getting used to its use in almost everything, which is why it becomes a mass consumption product with high demand. Considering the above, it has become almost essential for people to obtain it in many ways; One of them is the capture of solar rays through photovoltaic panels, since they are renewable and free of contaminants for both people and the environment. Through this project, the Antonio Nariño University at its Valledupar headquarters, aims to find spaces that provide the opportunity to have contact with human consciousness with respect to nature, through the use of renewable technology without affecting Biodiversity. For this reason, this project promotes the means and the way to implement resources that are used for the services of the computer room of block C. As an effect, the structural design, the design of the photovoltaic system and the internal electrical installation are acquired, with its according to studies. Through this document, exact data is consolidated, which highlights with greater precision the research on renewable energy issues, promoting sustainable development and climate change mitigation, guaranteeing the adequate use of these energies in the society of the alma mater of the Antonio Nariño University in Valledupar. Keywords: Electric energy, solar panels, renewable, photovoltaic, climate change.